Polysorbate 80 - Modulated nanocrystallization for enhancement of griseofulvin solubility - Emmanuel O. Olorunsola; Sifon Ekpeowo; Mumuni Momoh; Michael Adikwu (German Journal of Pharmaceuticals and Biomaterials, 2024)
Griseofulvin (GRFV1) is used in the treatment of many fungal infections, including ringworm and athlete's foot, as well as fungal infections of the scalp, fingernails, and toenails. However, its bioavailability is limited by poor water solubility. This work was aimed at improving the aqueous solubility of the drug via Polysorbate 80 - modulated nanocrystallization. Two types of nanocrystals (GRFV3 and GRFV2) were generated, respectively, with and without the inclusion of Polysorbate 80 in the nanocrystallization process. The three forms of the drug were subjected to a flowability test, differential scanning calorimetry, Fourier transform infrared spectroscopy, particle size analysis, and aqueous solubility determination. The flowability of the particles was in the order GRFV3 > GRFV2 > GRFV1. The thermogram of the drug powder showed a sharp endothermic transition with a peak at 75 ºC; that of the nanocrystals GRFV2 showed a single sharp endothermic transition with a peak at 170 ºC, while that of GRFV3 showed two endotherms with peaks at 75 ºC and 164 ºC. The nanocrystallization with or without a surfactant did not result in any observable change in the chemical integrity of the drug. The mean particle size was in the order GRFV3 < GRFV2 < GRFV1. There was a significant difference (P < 0.0001) in the aqueous solubility of the three forms of the drug, with GRFV3 having the highest value. Polysorbate 80 - modulated nanocrystallization can increase the aqueous solubility of griseofulvin by 4.14 folds; it is a potential way of improving the bioavailability of the drug.